Polymorphism of keratin-associated protein (KAP) 3.2 gene and its association with wool traits in Rambouillet sheep - MAHAJAN, VIKAS; DAS, A K; TAGGAR, R K; KUMAR, DHIRENDER; KUMAR, N (The Indian Journal of Animal Sciences, 2015)
In the present study, association of polymorphic variants of keratin-associated protein (KAP) 3.2 gene with wool traits in Rambouillet sheep was investigated. Genomic DNA was isolated from blood samples of 100 Rambouillet sheep. A 393 bp segment was amplified by PCR using ovine specific primers for KAP 3.2 gene. The genotyping was done by using PCR-SSCP. KAP 3.2 gene locus revealed 3 genotypes, viz. AA, AB and BB with genotype frequencies 0.46 (46), 0.40 (40) and 0.14 (14), respectively, with allele frequencies for allele A (0.66) and allele B (0.34). The result showed that the population was in Hardy-Weinberg equilibrium. Population genetic indexes such as expected heterozygosity (He) 0.45, effective number of alleles (ne) 1.81, Shannon indices (I) 0.64, Fixation index of individual with sub-population (FIS) 0.11, Standard error (SE) 0.03 and polymorphic information content (PIC) 35% were found. The least squares means of various genotypes for greasy fleece weight (GFW) differed significantly. The animals with AB genotype (2.08±0.08 kg) had higher GFW followed by AA genotype (1.75±0.08 kg), and BB genotypes (1.71Â±0.15 kg) was found to be associated. From the study, it may be concluded that KAP 3.2 gene might be a potential molecular marker for genetic selection in Rambouillet sheep.